Geometric properties for integro-differential operator involving the pre-Schwarzian derivative - Abdulnaby, Z.E.; Kılıçman, A.; Ibrahim, R.W. (Academic Press, 2016)
Recently, the study of operators theory (differential, integral, integro-differential) has been increased. It appears widely in the geometric function theory, to create some generalized subclasses of analytic functions. In this effort, we introduce a generalized integro-differential operator Jm(z) and obtain its properties by utilizing the pre-Schwarzian derivative. Applications are illustrated, based on fractional calculus in the sequel.